KOPI PAPUA: STRATEGI PEMBERDAYAAN ORANG ASLI PAPUA DALAM INDUSTRI KREATIF DI ERA OTSUS PAPUA - Elisabeth Lenny Marit (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
This paper aims to illustrate Papuan coffee made by indigenous Papuans (OAP) as part of creative industries in the era of Special Autonomy Papua. The facts show that 96 percent coffee plantation in Indonesia is a coffee plantation owned by around 1.7 million farmers families in Indonesia with production of about 0.72 tons per hectare. Based on the above description, half the coffee in Papua need revitalization because the coffee crop is not productive. The total area of coffee is 9,400 hectares in Jayawijaya, Tolikara, Puncak Jaya Lanny Jaya, Dogiyai, Deiyai and Paniai, 50 percent are unproductive. In terms of planting area is indeed an increase of 100 to 200 hectares per year. However, from the production side, Papua’s coffee is only 1,900 tons per year or the productivity of coffee is only 300 kilograms per year. The development of creative industries through Papuan coffee aims to (1) encourage the creation of the creative and socio-cultural sectors of the nation in the dignified Papua Land, and (2) contribute to the productivity of Papuan coffee.